2009
DOI: 10.1371/journal.pone.0007875
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Lack of a Direct Transcriptional Suppression of the Iron Regulatory Peptide Hepcidin by Hypoxia-Inducible Factors

Abstract: BackgroundHepcidin is a major regulator of iron metabolism and plays a key role in anemia of chronic disease, reducing intestinal iron uptake and release from body iron stores. Hypoxia and chemical stabilizers of the hypoxia-inducible transcription factor (HIF) have been shown to suppress hepcidin expression. We therefore investigated the role of HIF in hepcidin regulation.Methodology/Principal FindingsHepcidin mRNA was down-regulated in hepatoma cells by chemical HIF stabilizers and iron chelators, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 50 publications
3
85
0
Order By: Relevance
“…8 However, other studies in HepG2 cells showed that overexpression or knockdown of HIF-1 did not affect hepcidin expression 18 and have suggested indirect pathways including 2-oxoglutarate- 16 or ROS-dependent pathways. Moreover, HIF-2 but not HIF-1 seems to play a major role in iron metabolism and erythropoiesis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…8 However, other studies in HepG2 cells showed that overexpression or knockdown of HIF-1 did not affect hepcidin expression 18 and have suggested indirect pathways including 2-oxoglutarate- 16 or ROS-dependent pathways. Moreover, HIF-2 but not HIF-1 seems to play a major role in iron metabolism and erythropoiesis.…”
Section: Discussionmentioning
confidence: 95%
“…Whether hepcidin is regulated directly or through alternative pathways by HIF has been the subject of intense research in vitro. 10,[16][17][18] Our previous in vitro studies suggested a direct regulation of hepcidin by HIF. 8 However, our in vivo data could not exclude indirect alternative pathways.…”
Section: Hypoxia-inducible Factor-2α Is Not Involved In the Regulatiomentioning
confidence: 96%
“…25,26 Secreted protein expression was also increased throughout infection, albeit not as dramatically as mRNA. The latter may be due to post-transcriptional regulation of HAMP gene expression, including mRNA destabilisation 27 and secretion modulation. regulator in hepatocytes, 29 FPN was reduced during early infection.…”
Section: Discussionmentioning
confidence: 99%
“…2a). In agreement with published literature, these included hypoxia-inducible factor (HIF) (Volke et al, 2009) The AP1, C/EBP and STAT3 were mutated in the HAMPluc construct using the QuikChange kit (Agilent). Huh7 cells were co-transfected with each mutated reporter and core or core+1/ARFP expression vectors.…”
mentioning
confidence: 86%